Shear wave ultrasound elastography of the shoulder joint: Gender differences in KwaZulu-Natal, South Africa (African Journal of Biomedical Research, 2021)
Shear wave data for the rotator cuff and biceps tendons in asymptomatic individuals is limited in KwaZulu-Natal, South Africa. This study aimed to investigate the gender differences in tendon elasticity of the rotator cuff and biceps tendons using shear wave ultrasound elastography (SWUE). Rotator cuff and biceps tendons (sagittal and axial planes) of 260 patients (21-45 years), were evaluated using SWUE. An independent samples t-test was used to investigate whether differences in the tendon elasticity measurements for males and females exist. Gender based reference ranges for the mean elasticity of each tendon were found by constructing a 95% confidence interval. Gender differences for tendon elasticity were observed for the sagittal plane of the biceps tendon (proximal, middle and distal), the axial plane of the biceps tendon (middle) and the sagittal plane of the subscapularis tendon (middle). The sagittal supraspinatus (distal) and axial supraspinatus (middle) srevealed a significant gender difference in tendon elasticity. A significant gender difference in tendon elastcicity was noted for the teres minor tendon (axial and sagittal). Only the axial (proximal) region of the Infraspinatus tendon showed a significant gender difference in elasticity. Notably, males had higher mean elasticity values than the females in all the tendons that demonstrated significant elasticity differences. A non-invasive gender estimate of the elasticity of the rotator cuff and biceps tendons (kPa), is provided which may complement B-Mode ultrasound in the screening of rotator cuff and biceps tendon pathology.